Ensino híbrido: possíveis contribuições para a qualificação do ensino de história no ensino médio - Silva, Jorge Everaldo Pittan da (2016)
This study aims to investigate whether the implementation of activities based on hybrid education contribute to the qualifications of history teaching and learning in high school. Initially, an approach to history teaching over time reaching the present time, marked by the use of technology was made. In this context, it addresses the Hybrid Education, set of practices that seek to reconcile the use of digital technologies to the space of the traditional classroom. From this, it sought to organize activities informed the concepts of hybrid education, which were applied in groups 3º1 and 3º 3 High School State Institute of Education Teacher Annes Dias - Cruz Alta. Two models were developed: Reversed Classroom and rotation for seasons These activities were put in place having as a guiding principle of a Research Methodology Qualitative because not sought evidence closed data by numbers, but reflections from the observations made in classroom. The analysis served to verify that there really is a qualitative potential in the hybrid model, in that there was greater involvement of students, as well as enhancement of the teaching-learning process. However, there are still some limitations with regard to access to technology in schools, lack of teacher training in the use of digital resources and attachment of many students to the traditional teaching model, based on the teacher's idea as the center of the teaching process and learning.